Gene expression profiling of neural stem cells and their neuronal progeny reveals IGF2 as a regulator of adult hippocampal neurogenesis. - Bracko, Oliver; Singer, Tatjana; Aigner, Stefan; Knobloch, Marlen; Winner, Beate; Ray, Jasodhara; Clemenson, Gregory D.; Suh, Hoonkyo; Couillard-Despres, Sebastien; Aigner, Ludwig; Gage, Fred H.; Jessberger, Sebastian (Journal of Neuroscience, 2012)
Neural stem cells (NSCs) generate neurons throughout life in the hippocampal dentate gyrus (DG). How gene expression signatures differ among NSCs and immature neurons remains largely unknown. We isolated NSCs and their progeny in the adult DG using transgenic mice expressing a GFP reporter under the control of the Sox2 promoter (labeling NSCs) and transgenic mice expressing a DsRed reporter under the control of the doublecortin (DCX) promoter (labeling immature neurons). Transcriptome analyses revealed distinct gene expression profiles between NSCs and immature neurons. Among the genes that were expressed at significantly higher levels in DG NSCs than in immature neurons was the growth factor insulin-like growth factor 2 (IGF2). We show that IGF2 selectively controls proliferation of DG NSCs in vitro and in vivo through AKT-dependent signaling. Thus, by gene expression profiling of NSCs and their progeny, we have identified IGF2 as a novel regulator of adult neurogenesis.
EVALuna2:482722